Prophage-mediated defence against viral attack and viral counter-defence. - Dedrick, Rebekah M; Jacobs-Sera, Deborah; Bustamante, Carlos A Guerrero; Garlena, Rebecca A; Mavrich, Travis N; Pope, Welkin H; Reyes, Juan C Cervantes; Russell, Daniel A; Adair, Tamarah; Alvey, Richard; Bonilla, J Alfred; Bricker, Jerald S; et al. (Nature Microbiology, 2017)
Temperate phages are common, and prophages are abundant residents of sequenced bacterial genomes. Mycobacteriophages are viruses that infect mycobacterial hosts including Mycobacterium tuberculosis and Mycobacterium smegmatis, encompass substantial genetic diversity and are commonly temperate. Characterization of ten Cluster N temperate mycobacteriophages revealed at least five distinct prophage-expressed viral defence systems that interfere with the infection of lytic and temperate phages that are either closely related (homotypic defence) or unrelated (heterotypic defence) to the prophage. Target specificity is unpredictable, ranging from a single target phage to one-third of those tested. The defence systems include a single-subunit restriction system, a heterotypic exclusion system and a predicted (p)ppGpp synthetase, which blocks lytic phage growth, promotes bacterial survival and enables efficient lysogeny. The predicted (p)ppGpp synthetase coded by the Phrann prophage defends against phage Tweety infection, but Tweety codes for a tetrapeptide repeat protein, gp54, which acts as a highly effective counter-defence system. Prophage-mediated viral defence offers an efficient mechanism for bacterial success in host-virus dynamics, and counter-defence promotes phage co-evolution.
Keywords: *Mycobacteriophages/ph [Physiology]; *Mycobacterium smegmatis/vi [Virology]; *Mycobacterium tuberculosis/vi [Virology]; *Prophages/ph [Physiology]; DNA, Viral; DNA, Viral/ge [Genetics]; Genetic Variation; Genome, Bacterial; Genome, Viral; Ligases; Ligases/ge [Genetics]; Lysogeny; Mycobacteriophages; Mycobacteriophages/ge [Genetics]; Mycobacterium smegmatis; Mycobacterium smegmatis/ge [Genetics]; Mycobacterium tuberculosis; Mycobacterium tuberculosis/ge [Genetics]; Phylogeny; Prophages; Prophages/en [Enzymology]; Prophages/ge [Genetics]; Viral Proteins; Viral Proteins/ge [Genetics]; bacterial genome; dept.bio; enzymology; genetic variation; genetics; guanosine 3',5'-polyphosphate synthetases; ligase; lysogenization; mycobacteriophage; phylogeny; physiology; prophage; viral protein; virology; virus DNA; virus genome

Genomic diversity of bacteriophages infecting Microbacterium spp. - Jacobs-Sera, Deborah; Abad, Lawrence A; Alvey, Richard M; Anders, Kirk R; Aull, Haley G; Bhalla, Suparna S; Blumer, Lawrence S; Bollivar, David W; Bonilla, J Alfred; Butela, Kristen A; Coomans, Roy J; Cresawn, Steven G; et al. (PloS one, 2020)
The bacteriophage population is vast, dynamic, old, and genetically diverse. The genomics of phages that infect bacterial hosts in the phylum Actinobacteria show them to not only be diverse but also pervasively mosaic, and replete with genes of unknown function. To further explore this broad group of bacteriophages, we describe here the isolation and genomic characterization of 116 phages that infect Microbacterium spp. Most of the phages are lytic, and can be grouped into twelve clusters according to their overall relatedness; seven of the phages are singletons with no close relatives. Genome sizes vary from 17.3 kbp to 97.7 kbp, and their G+C% content ranges from 51.4% to 71.4%, compared to ~67% for their Microbacterium hosts. The phages were isolated on five different Microbacterium species, but typically do not efficiently infect strains beyond the one on which they were isolated. These Microbacterium phages contain many novel features, including very large viral genes (13.5 kbp) and unusual fusions of structural proteins, including a fusion of VIP2 toxin and a MuF-like protein into a single gene. These phages and their genetic components such as integration systems, recombineering tools, and phage-mediated delivery systems, will be useful resources for advancing Microbacterium genetics.
Keywords: *Actinobacteria/vi [Virology]; *Bacteriophages/ge [Genetics]; *Genetic Variation; *Genome, Viral; Actinobacteria; Article; Bacteriophages; Bacteriophages/cl [Classification]; Bacteriophages/ip [Isolation & Purification]; Base Composition; DNA base composition; DNA, Viral; DNA, Viral/ge [Genetics]; Genes, Viral; Genetic Variation; Genome, Viral; Genomics; Microbacterium; MuF like protein; Phylogeny; VIP2 toxin; Viral Fusion Proteins; Viral Fusion Proteins/ge [Genetics]; bacterial genome; bacterial strain; bacterial toxin; bacteriophage; capsid protein; classification; comparative genomics; controlled study; dept.bio; fusion protein; gene sequence; genetic variability; genetic variation; genetics; genome size; genomics; isolation and purification; nonhuman; nucleotide sequence; peer-reviewed; phylogeny; unclassified drug; virology; virus DNA; virus fusion protein; virus gene; virus genome; virus infection; virus isolation

Models of classroom assessment for course-based research experiences - Hanauer, David I.; Zhang, Tong; Graham, Mark J.; Adams, Sandra D.; Ahumada-Santos, Yesmi Patricia; Alvey, Richard M.; Antunes, Mauricio S.; Ayuk, Mary A.; Elena Báez-Flores, María; Bancroft, Christa T.; Bates, Tonya C.; Bechman, Meghan J.; et al. (Frontiers in Education, 2023)
Course-based research pedagogy involves positioning students as contributors to authentic research projects as part of an engaging educational experience that promotes their learning and persistence in science. To develop a model for assessing and grading students engaged in this type of learning experience, the assessment aims and practices of a community of experienced course-based research instructors were collected and analyzed. This approach defines four aims of course-based research assessment—(1) Assessing Laboratory Work and Scientific Thinking; (2) Evaluating Mastery of Concepts, Quantitative Thinking and Skills; (3) Appraising Forms of Scientific Communication; and (4) Metacognition of Learning—along with a set of practices for each aim. These aims and practices of assessment were then integrated with previously developed models of course-based research instruction to reveal an assessment program in which instructors provide extensive feedback to support productive student engagement in research while grading those aspects of research that are necessary for the student to succeed. Assessment conducted in this way delicately balances the need to facilitate students’ ongoing research with the requirement of a final grade without undercutting the important aims of a CRE education.
Keywords: dept.bio; peer-reviewed